Integrating Religious Culture In Growing Islam Rahmatan Lil 'Alamin At SMP Negeri 1 Sumbermalang Situbondo - Efendi, Ridwan (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
This study aims to describe the process of integrating religious culture in growing Islam rahmatan lil 'alamin students at SMP Negeri 1 Sumbermalang. In this study, the research approach uses descriptive qualitative. The results of the research show that the pattern of implementing integralistic education at SMP Negeri 1 Sumbermalang is to integrate Islamic values ​​in each subject with efforts to read prayers and sholawat nariyah which are required to be read in every activity in the school. The number of readings of sholawat nariyah is 3 times with the aim of hoping for intercession to the Prophet Muhammad SAW so that students can be given convenience in carrying out the learning process in the classroom and the knowledge that has been obtained can be practiced in everyday life.